Optimism and auditor liability. Issue 6 (18th September 2016) - Bigus, Jochen
Abstract : There is strong evidence that individuals are optimistic in the sense that they underrate the probability of a negative event occurring. This paper provides a positive theoretical analysis of how auditor optimism affects their incentives to take care under two liability rules: strict liability and a negligence rule. Under strict liability, auditors are held liable when they cause damages to investors. Under a negligence rule, auditors are held liable when they cause damages and in addition, act negligently, that is, fail to meet the standard of due care specified in legal and professional rules. I find the following results. (1) If due care is sufficiently close to the efficient level, a negligence rule distorts auditors' incentives less than strict liability. Under strict liability, optimism makes the auditor overestimate the chances of finding material mistakes and thus induces suboptimal care. (2) If due care is too strict, the auditor will not exert due care but the same level of suboptimal care under either liability rule. (3) With increasing optimism and in the absence of punitive damages, strict liability becomes less preferable to a precise negligence rule. This statement also holds for vaguely defined standards of due care if due care is sufficiently strict or if auditor optimism is sufficiently high. (4) Punitive damages counteract suboptimal incentives generated by auditor optimism, especially under strict liability.